Phytogeographic Studies on the Western Satpuda Mountains of Khandesh Region in Maharashtra - Thomas, J.; Yadav, S. S.; Varghese, M. (Indian Forester, 2005)
The flora of western Satpuda in the Khandesh Region holds a dual position having affinities with neighbouring floristic regions. Phytogeographical studies on the western Satpuda Mountains have shown that the region contains three groups of floristic elements spread in twenty categories, namely un-, bi- and pluri-regional elements. Among the uniregional group, the most common element is Indian (34.30%) followed by pantropical (10.44%) and paleotropic (10.04%) of pluri-regional group. Although the region has a number of other floristic elements, most of them do not have any appreciable contribution in the mountains. The study area does not contain any endemic species of its own. however, western Satpuda is acting as a refuge for some of the most endangered species of Maharashtra State and also as a centre of speciation and dispersal for African and Malayan elements.